Shadow as Trigger Factor of Morality Change in Utopian Society in From the New World Novel - Muhammad Yandi (Faculty of Letters Universitas Balikpapan, 2020)
This research aims to analyze the role of shadow towards the morality change in a utopian society in the novel From the New World by Yusuke Kishi. The focus is to identify the factors of shadow within the novel and to find how shadow triggers morality change in utopian society within the novel. The theory used in this research is psychoanalysis by Carl Jung, specifically shadow and morality. Shadow was used to examine the atrocities conducted within the novel and Carl Jung’s approach of morality was used to examine the morality change phenomenon in utopian society within the novel. The method used in this research is qualitative in a descriptive way. The researcher found the factors of shadow as ego, personal unconscious, and dark aspects of personality. Each of these factors is integral in how shadow triggers morality change in utopian society and the resulting changes found are within social, sexual, and intuitive morality. The research shows that shadow is the primary cause of morality changes happening within the novel and this research aims to prove whether shadow could be repressed in order to achieve perfect morality.